Le care en éducation : aspects institutionnels et politiques - Roger Monjo (Éducation et Socialisation)
Firstly, we will examine the care theories in a context characterized by the criticisms directed to the theories of justice from contractualist (Kantian) inspiration in order to determine the status of the former in relation to the latter. Are the care theories a genuine alternative or a means to re-orientate the theories of justice by completing them ? This second option, by giving a political scope to the ethical issues raised by the care theories will actually prevent any paternalistic and compassionate drifts which are a threat to them. Secondly, we will tackle the possible application of these approaches to the field of school education. This will be done in a propaedeutic manner insofar as we will mainly point out the obstacles which might prevent this application to produce emancipating, socially progressist and really positive effects.